Digital labor trapped in “audience metrics”: the professional identity and confusion of Chinese journalists - Dong, Yan; Mohd Zawawi, Julia Wirza; Haji Bidin, Rosmiza; Syed Alsagoff, Syed Agil (Redfame Publishing, 2026)
With the advent of social media, the work of journalists is no longer limited to news interview and writing, and artificial intelligence technology is increasingly applied to news gathering and information distribution. These digital platforms and emerging technologies have brought unprecedented changes to journalism. Through in-depth interviews with 23 Chinese new media journalists, this study conducted a qualitative analysis to explore the interaction between journalists’ role perception, professional identity and continuous changes in the industry in the digital media era. The research finds that at the level of news production, journalists seek the balance and self-consistency of “adhering to traditional news values and pursuing traffic and audience goodwill” in the daily high-intensity KPI workload. The unequal ability to use technology and the pressure of traffic competition make journalists confused about their role perception. The weakening of professional concept and the gradual loss of professional spirit have caused the crisis of journalists’ professional cognition. The continuously transforming environment of China’s news industry urgently needs to reflect and re-examine the erosion of the public value of journalism by the market and audience.